A tributação de criptoativos à luz da justiça fiscal - Makiya, Erick Hitoshi Guimarães (2023)
The theme to be addressed in this research revolves around the analysis of technological and economic development generated by operations involving crypto assets and the lack of appropriate tax treatment, from the perspective of tax justice theory. Thus, the delimitation of the theme is carried out in the investigation of the economic development generated by the trade of crypto assets, focusing on the necessary tax adjustments to ensure that all individuals share the benefits of this new economy and wealth, even through state intervention in the form of taxation. In this sense, the delimitation of the theme consists, initially, in the assessment and demonstration of the development of this new economy, especially in manifestations of wealth arising from various operations involving crypto assets. Secondly, in demonstrating that such development, despite being poorly regulated, is beneficial to society, provided that its benefits are shared fairly among individuals. Finally, in a third moment, in the analysis of a way to share the benefits of development, especially those related to crypto assets, through taxation, since one of its functions is precisely to ensure the realization of fundamental rights provided for in the constitutional text.